Neuropsychological, psychometric and autonomic correlations in patients with duodenal ulcer. - Demydas, Olena; Tkachenko, Олена (Psychosomatic Medicine and General Practice, 2023)
The aim is to study neuropsychological, psychometric and autonomic correlations in patients with duodenal ulcer. Materials and methods. We conducted a comprehensive clinical and neurological examination of 84 patients with duodenal ulcer in the acute stage, and 84 of them again in the remission stage of the disease. The patients' age ranged from 25 to 60 years, the average age was (39.90 ± 1.29) years. There were 61 men (72.6%) and 23 women (27.4%). All subjects were divided into two groups based on the presence of exacerbation or remission of peptic ulcer disease. All patients underwent a detailed interview using a specially designed questionnaire, which analyzed the main psychosomatic complaints. To study the neuropsychological characteristics, patients underwent neuropsychological testing, which included determining the levels of constitutional and reactive anxiety according to the Spielberger-Hanin scale, the level of depression according to the Beck scale, assessment of cognitive impairment using the MMSE scale, assessment of the speed of attention switching and the dynamics of performance using Schulte tables. The study of vegetative status was carried out using the O.M. Wayne questionnaire. Results. In patients with UC in the acute stage, a correlation of medium strength between the level of personal anxiety and the detection of cognitive impairment by the MMSE scale was established (r=0.53). There was also a correlation between the level of depression and the detection of cognitive impairment by the MMSE scale in patients with UC PDA in the acute stage (r=0.49). It was found that cognitive performance in patients with UC is related to the level of anxiety and severity of depressive disorders, and with a decrease in their symptoms, there is an improvement in cognitive function. A direct correlation between the number of points obtained on the objective scale of the Wayne's questionnaire and the level of personality (r=0.61), reactive anxiety (r=0.59) and depression (r=0.53) was found in patients with UC in the acute stage. A direct correlation was found in patients with UC UC in the acute stage between the number of points obtained on the objective scale of the Wayne's questionnaire and the detection of cognitive impairment on the MMSE scale (r=0.46). A direct correlation (r=0.42) was also established between the performance indicators determined by the Schulte tables and cognitive changes detected by the MMSE scale in patients with UC in the acute stage. It was found that the degree of inclusion in work according to the Schulte tables slows down in the presence of cognitive impairment, determined by the MMSE scale. The degree of inclusion in work had a relationship (r=0.40) with cognitive impairment detected by the MMSE scale. In patients with UC UC in the acute stage with predominance of sympathicotonia, a decrease in the ability to concentrate attention was most often detected. Conclusions. The results of the correlation analysis indicate the interdependence between anxiety-depressive, autonomic disorders and indicators of cognitive status in patients with UC PSC.